1) To get equation B from equation A, we will add a quantity to the left hand side of equation A. The correct option is A. Add/subtract a quantity to/from only one side
2) The equations are not equivalent. They do not have the same solution
<h3>Equations</h3>
From the question, we are to determine how we can get equation B from equation A
From the given information,
A. 5x - 2 + x = x - 4
B. 5x + x = x - 4
From above, we can observe that to get equation B from equation A, we will add 2 to the left hand side of equation A
That is
5x - 2 + 2 + x = x + 4 → 5x + x = x + 4
Hence, to get equation B from equation A, we will add a quantity to the left hand side of equation A. The correct option is A. Add/subtract a quantity to/from only one side
2) The equations are not equivalent. They do not have the same solution
Learn more on Equations here: brainly.com/question/21765596
#SPJ1
Answer:
67
Step-by-step explanation:
2x3=6
402/6=67
2x3x67=402
hope this helped:)
The given equation is
To solve for x, we have to subtract 8 to both sides
Now we need to get rid of -9 from the left side, and for that we do division
Create a ratio and cross multiply
20x - 75 = 14x + 63
6x = 138
x=23
hope this helps :)
About 90 maybe but not sure